Introduction to Cyberterrorism in Indonesia - Delvin; Yonky Pernando (IAM Indonesia, 2023)
In the 21st century, the development of cyber technology has had a significant impact on human life. However, this progress has also brought negative implications, including cybercrimes such as data theft, the distribution of pornography, and online fraud. Cybercrimes have evolved into the form of cyberterrorism, where terrorists utilize the internet and information technology to carry out attacks. Cyberterrorism has become a serious threat in the digital era. Terrorists have modified their communication techniques by targeting and utilizing the internet. They also incorporate artificial intelligence technology into their cyberterrorism operations. Furthermore, terrorist groups often exploit social media platforms to propagate their ideologies and recruit new followers. The government of Indonesia has made various efforts to combat cyberterrorism, including the establishment of the National Cyber and Crypto Agency (BSSN) and the implementation of regulations, such as amendments to the Electronic Information and Transactions Law (ITE Law), to prevent cybercrimes and cyberterrorism. This research employs normative research methods to analyze the application of relevant laws and norms. The analysis results indicate that cyberterrorism is a significant threat. The government has taken essential steps to address it, but cyberterrorism continues to evolve and requires continuous monitoring and cooperation between the government, law enforcement agencies, and the private sector. In conclusion, cyberterrorism is a real threat in today's digital era. The findings of this research can provide guidance to the government in developing more effective policies and regulations to address cyberterrorism.